PEMBELAJARAN SENI KALIGRAFI ISLAM (KHAT) UNTUK MENINGKATKAN MAHARAH AL-KITABAH (KETERAMPILAN MENULIS) - WAHYUDI, WALUYO ERRY (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2024)
Calligraphy is a lesson given by schools to students. By providing calligraphy lessons, it also trains them to be able to write Arabic letters well so that there are no misreadings, meanings and interpretations. It is hoped that calligraphy lessons can contribute to the lessons of the Qur'an and Hadith on students' writing skills. Therefore, research related to the importance of studying Islamic calligraphy art in the practice of students' Arabic writing skills was conducted. This study aims to 1) understand Maharah al-Kitabah in Islamic Calligraphy learning 2) how is the process of implementing Islamic calligraphy learning 3) are there any inhibiting and supporting factors in the implementation of Islamic Calligraphy Learning. Observation, interviews and documentation are the methods chosen in this study. Data obtained during the investigation were reviewed through data reduction, data percentages and summarizing conclusions. While the validity experiment of a number of data was collected and worked on by triangulation and observation. The results of this observation show several things, including: 1) in the process of implementing teaching and learning in calligraphy lessons, it is carried out in a stable and systematic manner in accordance with the beginning of the learning process from the beginning to the end, starting from the opening or introduction, the core learning process, and the closing section. 2) the calligraphy learning process is developed by educators, infrastructure is provided by the school because many students do not have materials and tools to make calligraphy, that is the main key to a good calligraphy learning process. ABSTRAKKaligrafi merupakan  pelajaran yang diberikan sekolah kepada peserta didik. Dengan memberikan pelajaran kaligrafi juga melatih supaya bisa writing huruf Arab dengan baik hingga tak menghadirkan salah membaca, makna dan interprestasi. Diharapkan Pelajaran kaligrafi dapat menghadirkan sumbangsih pada pelajaran Alqur`an hadits pada keterampilan writing peserta didik. Oleh karena itu penelitian yang berkaitan dengan pentingnya mempelajari seni kaligrafi Islam didalam praktik keterampilan writing Arab peserta didik dilakukan. Penelitian ini bertujuan 1) agar dapat mengerti  Maharah al-Kitabah  dalam pembelajaran Kaligrafi Islam 2) bagaimana dalam proses penerapan pembelajaran kaligrafi Islam 3)apakah ada faktor-faktor penghambat juga pendukung dalam penerapan Pembelajaran Kaligrafi Islam. Observasi, interview dan dokumentasi merupakan metode yang dipilih dalam penelitian ini. Data didapat selama investigasi ditelaah melalui pengecilan data, persentasi dalam data serta merangkum kesimpulan. Sedangkan percobaan validitas sejumlah data dikumpulkan dan dimkerjakan dengan cara triangulasi serta observasi. Hasil dari observasi ini menunjukkan beberapa hal diantara lain: 1) dalam proses implementasi belajar mengajar dalam pelajaran kaligrafi dilaksanakan dengan cara tetap stabil juga bersistem sesuai dengan pemulaan proses pembelajaran dari awal samapai akhir mulai dari pembukaan atau pendahuluan, proses inti pembelajaran, serta bagian penutup. 2) proses belajar kaligrafi dikembangkan oleh Pendidik, sapras di sediakan oleh pihak sekolah dikarenakan peserta didik banyak yang tidak memiliki bahan dan alat dalam membuat kaligrafi, itu adalah kunci utama proses pembelajaran kaligrafi yang baik.